Corporate Social Responsibility Practices, Corporate Sustainable Development, Venture Capital and Corporate Governance: Evidence from Chinese Public Listed Firms - Jing Wu,; Chee Yoong Liew, (Asian Academy of Management Journal of Accounting and Finance, 2024)
This study intends to investigate the relationship between the different corporate social responsibility (CSR) practices of firms and their corporate sustainable development (CSD) as well as whether venture capital (VC) and corporate governance (CG) moderate this relationship and capital allocation efficiency (CAE) mediates the relationship. The sample of this study consist of Chinese A-share public-listed firms as well as the Growth Enterprise Market (GEM) listed firms in China. The duration covered is from 2013 to 2020. There are significant positive relationships between CSR and CSD among Chinese A-shares listed firms and GEM listed firms. In addition, there is a significant positive moderating effect of CG and no significant moderating effect of VC on the relationship between CSR and CSD among Chinese A-shares listed firms. However, for GEM listed firms, there is no significant moderating effect of both VC and CG on the relationship between CSR and CSD. Finally, there is a significant positive mediating effect of CAE on the relationship between CSR and CSD among Chinese A-shares listed firms and GEM listed firms.